Patrones de abundancia y actividad del lince (Lynx rufus; Schreber, 1777) en dos hábitats contrastantes del centro de México - Flores Torres, José Yoani (Universidad Michoacana de San Nicolás de Hidalgo, 2021)
Central Mexico is one of the most fragmented regions of the country and also one of the most important areas in the distribution of the lynx (Lynx rufus). The patterns of abundance and activity of the lynx tend to vary due to various factors associated with the characteristics of the habitat, interactions or human activity; however, these patterns have not been analyzed and compared between contrasting habitats in central Mexico. Therefore, the objective of this study was to determine the factors that influenced the relative abundance and activity patterns of the lynx with respect to the different interaction groups (potential prey, competitors and domestic species) during the two most marked seasons of the year. year (dry and wet) for a temperate forest and a semi-arid scrub in central Mexico. We exclusively use the photo-trapping method in a two-year sampling period (2016-2017 and 2019-2020). The composition and abundance of the community of species registered in each habitat, the specific richness and the capture rate were evaluated. The activity patterns of the lynx and overlap with the rest of the species were evaluated with the Overlap statistical package of the R version 3.6.3 software. With a total sampling effort of 6,622 trap nights, 8,190 independent records were generated, of which 310 and 55 correspond to the lynx for the temperate forest and semi-arid scrub, respectively. The rest of the records correspond to 30 species (18 of medium and large wild mammals, 7 species of domestic mammals and 5 species of birds).

El centro de México es una de las regiones más fragmentadas del país y también una de las zonas más importantes en la distribución del lince (Lynx rufus). Los patrones de abundancia y actividad del lince suelen variar por diversos factores asociados a las características del hábitat, interacciones o actividad humana, sin embargo, estos patrones no han sido analizados y comparados entre hábitats contrastantes del centro de México. Por lo tanto, el objetivo de este estudio fue determinar los factores que influyeron en la abundancia relativa y los patrones de actividad del lince con respecto a los diferentes grupos de interacción (presas potenciales, competidores y especies domésticas) durante las dos temporadas más marcadas del año (seca y húmeda) para un bosque templado y un matorral semiárido del centro de México. Utilizamos exclusivamente el método de fototrampeo en un periodo de dos años de muestreo (2016-2017 y 2019-2020). Se evaluó la composición y abundancia de la comunidad de especies registrada en cada hábitat mediante la riqueza específica y la tasa de captura. Los patrones de actividad del lince y traslape con el resto de las especies, fueron evaluados con el paquete estadístico Overlap del software de R versión 3.6.3. Con un esfuerzo total de muestreo de 6,622 noches-trampa se generó 8,190 registros independientes de los cuales 310 y 55, correspondieron al lince para el bosque templado y matorral semiárido respectivamente. El resto de registros corresponden a 30 especies (18 de mamíferos silvestres de talla mediana y grande, 7 especies de mamíferos domésticos y 5 especies de aves).
Instituto de Investigaciones Agropecuarias y Forestales. Facultad de Biología. Facultad de Medicina Veterinaria y Zootecnia. Facultad de Agrobiología. Facultad de Químico Farmacobiología. Programa Institucional de Maestría en Ciencias Biológicas
Keywords: info:eu-repo/classification/cti/6; FB-M-2021-0949; Ecología y conservación; Fototrampeo; Abundancia relativa; Patrones de actividad; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/6437